Pengaruh Kemampuan Akuntansi Dasar, Motivasi Belajar, dan Persepsi Siswa tentang Metode Mengajar Guru terhadap hasil Belajar Pratikum Akuntansi Dagang - Annesi Ismi; Syamwil Syamwil (Jurnal Ecogen, 2021)
The purpose of this research is to determine the effect of introduction of accounting skills, learning motivation, and students perceptions of teacher teaching methods on the learning outcomes of marchandise accounting practicum. This research is a descriptive and associative. This research implemented on student class XI Accounting at SMK N 2 Padang. The Sample used in this study is 107 students using simple random sampling technique form 146 population. Data collected with test and questionnaires and analysis of data using multiple regresion analysis. The results show that 1)introduction of accounting skills, learning motivation, and students perceptions of teacher teaching methods have a significant effect on the learning outcomes of marchandise accounting practicum 2)introduction of accounting skills have a significant effect on the learning outcomes of marchandise accounting practicum 3)learning motivation have a significant effect on the learning outcomes of marchandise accounting practicum and 4)students perceptions of teacher teaching methods have a significant effect on the learning outcomes of marchandise accounting practicum with a coefficient determination (R2) of 50,4 Keywords : introduction of accounting skills, learning motivation, and students perceptions of teacher teaching methods